2007
DOI: 10.1002/adfm.200601042
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Luminescent Gels Containing Metal Complexes

Abstract: Gelators are compounds capable of solidifying various solvents and water. Organic gels, and in particular hydrogels, are interesting soft materials with many potential applications. In this paper the formation of luminescent gels in water and dimethylformamide as solvents is reported. The gels are prepared by using a carboxylate‐based aliphatic gelator (1) and a N,N′‐bis(O‐methyl‐TyrOH) oxalamide derivative (2). The gels are transparent, and form fiberlike structures in the presence of the red luminescent moie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…It is believed that it is such an arrangement that leads to the formation of the microparticles, which are characterized by a hydrophobic surface. Similar discoveries have been reported by other groups [57]. Although FTIR spectroscopy is thought to be a powerful tool for studying hydrogen bonding interactions among gelator molecules in organic solvents, it is very difficult to obtain similar information from systems containing water.…”
Section: Spectroscopic Studiessupporting
confidence: 54%
“…It is believed that it is such an arrangement that leads to the formation of the microparticles, which are characterized by a hydrophobic surface. Similar discoveries have been reported by other groups [57]. Although FTIR spectroscopy is thought to be a powerful tool for studying hydrogen bonding interactions among gelator molecules in organic solvents, it is very difficult to obtain similar information from systems containing water.…”
Section: Spectroscopic Studiessupporting
confidence: 54%
“…There are only few reports on lanthanide ion‐doped supramolecular gels. For example, europium‐complex‐based gels have been synthesized by mixing the gelators with the europium complex and their luminescence properties studied 21. Maitra et al.…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, very few studies of lanthanide-complex gel have been reported [9,10]. In this report, we studied four luminescent organogels based on urea derivatives N,N 0 -dioctadecylurea 1 and N-octadecylurea 2 (the structures are shown in Fig.…”
Section: Introductionmentioning
confidence: 98%
“…Luminescence gels have been reported to form through two different approaches. The one is that the gelators possess photoactive units in their chemical structures and the other is photoactive molecules being hosted in the gel network [9]. As is known to us all, lanthanide complexes can exhibit emission in organic media.…”
Section: Introductionmentioning
confidence: 99%